2017
DOI: 10.1016/j.addbeh.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe smoking patterns and symptoms of nicotine dependence: The Waterpipe Dependence in Lebanese Youth Study

Abstract: Introduction Waterpipe typically is smoked intermittently over long smoking sessions. Waterpipe is addictive and its users show symptoms of nicotine dependence (ND). This study examined the risk of developing ND symptoms across waterpipe use patterns among Lebanese youth. Methods Waterpipe use patterns (length of smoking session, smoking a whole waterpipe without sharing, past-30 day use frequency, number of waterpipes smoked) were assessed. Symptoms of ND were assessed using the 10-item Hooked on Nicotine C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Its prevalence is also rising among adolescents (3.9% frequent smokers in 2012), especially in the presence of a family member or friend who smokes [26]. Similarly, the prevalence of waterpipe use is high in Lebanon, with up to 35% of the 13 to 15 years old category having already used it [27]. Actually, waterpipes are more appealing to adolescents due to the different flavors and look, and due to the false idea of waterpipe smoking being a non-harmful method [28], its use in adolescent population is popular [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence is also rising among adolescents (3.9% frequent smokers in 2012), especially in the presence of a family member or friend who smokes [26]. Similarly, the prevalence of waterpipe use is high in Lebanon, with up to 35% of the 13 to 15 years old category having already used it [27]. Actually, waterpipes are more appealing to adolescents due to the different flavors and look, and due to the false idea of waterpipe smoking being a non-harmful method [28], its use in adolescent population is popular [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…We use these factors since they perform well in traditional tobacco prediction research and represent standard factors for the desire for women to smoke waterpipe [2,16]. Another rational is that these factors also cover experiencing cravings that leads them to smoke waterpipe [17,20]. It was demonstrated that young initiation age of smoking linked to being a regular smoker at a later age [17,18,19].…”
Section: B Classification Factorsmentioning
confidence: 99%
“…Another rational is that these factors also cover experiencing cravings that leads them to smoke waterpipe [17,20]. It was demonstrated that young initiation age of smoking linked to being a regular smoker at a later age [17,18,19]. Moreover, it was shown that number of tobaccos smoked significantly related to level of nicotine dependence [17,21,25,29,30].…”
Section: B Classification Factorsmentioning
confidence: 99%
“…Lebanon is smoking prevalence ranks first in the Middle East and for Arab females, with 43% of men and 28% of women in Lebanon being smokers 13 . Waterpipe smoking prevalence is high in Lebanon especially in youth, with 35% of teens aged between 13 and 15 having used it; among them, 47% smoked less than once weekly, 38% weekly but not daily, 16% daily 14 . A study showed that divorce increased the risk of drinking and smoking initiation 15 .…”
Section: Introductionmentioning
confidence: 99%